Związek powiatowo-gminny jako nowy model formy współpracy jednostek samorządu lokalnego - Sikora, Kamil; Stelmasiak, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Since 2016, it has become possible to create poviat and commune unions as a new form of cooperation between local government units. Until now, it was legally permissible to create unions in the so-called horizontal, between communes — as inter-communal unions, between poviats as poviat unions. Poviat and commune unions are a form of cooperation in the so-called vertical. Thus, cooperation may develop not only horizontally, but also vertically between commune and poviat units. The procedure for establishing a poviat-commune union is analogous to the procedure for establishing a poviat-commune union, except that in the procedure for agreeing the draft statute of a poviat-commune union, poviats and communes intending to establish a union are represented by the starost of one of the poviats or the head of one from among the communes authorized by starosts and voices of the remaining counties and communes. A poviat and commune union is an organizational and legal form of joint performance of public tasks by poviats and communes. The union performs public tasks on its own behalf and under its own responsibility, has legal personality, and may act as an independent subject of rights and obligations in legal transactions. By the end of March 2021, a total of 13 poviat and commune associations were registered.
Keywords: poviat and commune union; register of poviat and commune associations; statute of a poviat and commune union; tasks of a poviat and commune union; commune as a local governmentunit